Pendampingan Anak Disabilitas Melalui Olahraga Adaptif Berbasis Permainan Untuk Kebersamaan Dan Toleransi - Berto Apriyano; Riski Rinaldi; M. Fachri Rahman; Sribulan Rosandi; Adiba Yufi; Deti Rahmah Hidayati; Hekiss Trishandy; Elfina Elfina; Muhammad Frans; Muhammad Iwang Ferdianto (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service activity aims to foster values of togetherness and tolerance among children with disabilities through adaptive sports based on educational games. The method used is a participatory approach, involving children with disabilities in various game-based activities that have been modified according to their abilities and needs. The program was implemented in several stages, including planning, execution, and evaluation, with the involvement of facilitators and educators. The results indicate that adaptive sports based on educational games are effective in creating an inclusive and engaging environment, enhancing social interaction, and promoting mutual respect among participants. In addition, improvements were observed in self-confidence, cooperation, and motor skills of the children. Therefore, this approach is effective as a learning medium that not only focuses on physical aspects but also strengthens social values.